Polo Acuña, José Trinidad. Indígenas, poderes y mediaciones en La Guajira en la transición de la colonia a República (1750-1850). Bogotá: Ediciones Uniandes, 2012. 398 pp. - Daza Villar, Vladimir; Universidad de Caldas (2017)
null